2020
DOI: 10.1097/qai.0000000000002237
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz-Based Antiretroviral Therapy Reduces Artemether–Lumefantrine Exposure for Malaria Treatment in HIV-Infected Pregnant Women

Abstract: Background:The choice of malaria treatment for HIV-infected pregnant women receiving efavirenz-based antiretroviral therapy must consider the potential impact of drug interactions on antimalarial exposure and clinical response. The aim of this study was to investigate the effects of efavirenz on artemether-lumefantrine as no studies have isolated the impact of efavirenz for HIVinfected pregnant women. Methods:A prospective clinical pharmacokinetic (PK) study compared HIV-infected, efavirenztreated pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Clinical trial simulations based on the final PK/PD models found that extending treatment to 5 or 7 days would equalize lumefantrine exposure between those receiving an interacting ART regimen, and those who do not take these drugs. Although the studies discussed above enrolled adult patients, similar results have been seen in children and pregnant women indicating the universal benefit of dosing changes for all patient populations 50‐56 . In addition to testing these novel regimens, the importance of designing the next set of clinical trials to collect and integrate treatment outcome data should not be overlooked.…”
Section: Act Drug‐drug Interactionsmentioning
confidence: 85%
See 1 more Smart Citation
“…Clinical trial simulations based on the final PK/PD models found that extending treatment to 5 or 7 days would equalize lumefantrine exposure between those receiving an interacting ART regimen, and those who do not take these drugs. Although the studies discussed above enrolled adult patients, similar results have been seen in children and pregnant women indicating the universal benefit of dosing changes for all patient populations 50‐56 . In addition to testing these novel regimens, the importance of designing the next set of clinical trials to collect and integrate treatment outcome data should not be overlooked.…”
Section: Act Drug‐drug Interactionsmentioning
confidence: 85%
“…Although the studies discussed above enrolled adult patients, similar results have been seen in children and pregnant women indicating the universal benefit of dosing changes for all patient populations. 50 , 51 , 52 , 53 , 54 , 55 , 56 In addition to testing these novel regimens, the importance of designing the next set of clinical trials to collect and integrate treatment outcome data should not be overlooked. Along with understanding how DDIs impact antimalarial PK exposure, it is equally important to understand their effects on parasite clearance rates and treatment outcomes.…”
Section: Act Drug‐drug Interactionsmentioning
confidence: 99%
“…7 The findings among children in Uganda and Malawi were likely a result of the pharmacokinetic interaction between LPV/r and lumefantrine rather than between efavirenz and artemether. 20 In adults, no difference in malaria incidence was observed in women receiving a PI-based vs. nNRTI-based ART. 8…”
Section: Discussionmentioning
confidence: 98%
“…7 The findings among children in Uganda and Malawi were likely a result of the pharmacokinetic interaction between LPV/r and lumefantrine rather than between efavirenz and artemether. 20 In adults, no difference in malaria incidence was observed in women receiving a PI-based vs. nNRTI-based ART. 8 We did not find a statistically significant difference in parasite clearance rates nor in time-to-parasite clearance between PI and nNRTI treatment arms.…”
Section: Discussionmentioning
confidence: 98%
“…AUC and C max ratios (German et al, 2009). Contrastingly, other studies found that co-treatment of artemether-lumefantrine with efavirenz significantly decreased artemisinin and lumefantrine bioavailability and total exposure (E. Hughes et al, 2020), highlighting that different anti-retroviral influence anti-malarial drug metabolism differently.…”
Section: Co-morbidities and Combination Of Antimalarial Drugs With Ot...mentioning
confidence: 88%